Jatrorrhizine Hydrochloride alleviates tert-butyl hydroperoxide-induced endothelial cell injury through its anti-inflammatory activity and PPAR-Î³ activation - Wu, Guanji; Mu, Ting; Zhang, Lihong; Chen, Xiaolin (Cellular and Molecular Biology, 2020)
The aim of this study was to investigate whether Jatrorrhizine hydrochloride (JAH) can attenuate oxidative damage of endothelial cells by regulating mitochondrial function and inflammatory response. It was found that JAH inhibited tert-butyl hydroperoxide (t-BHP)-induced oxidative damage in mouse brain endothelial cells (MBECs) by increasing cell viability and inhibiting cell apoptosis. Moreover, JAH significantly inhibited the production of reactive oxygen species (ROS) and lipid peroxidation. It enhanced mitochondrial membrane potential (MMP) and maintained ATP synthesis. In addition, JAH regulated the expressions of inflammatory cytokines and increased the activation of endothelial nitric oxide synthase (eNOS). The protective effect of JAH was related to the protein expression of peroxisome proliferator-activated receptor-Î³ (PPAR-Î³) gene. In conclusion, these results suggest that JAH may have therapeutic potential for ischemic stroke associated with endothelial dysfunction through its antioxidant and anti-inflammatory properties.